Music of the first nations : tradition and innovation in native North America - Browner, Tara, 1960- (Music in American life., 2009)
This unique anthology presents a wide variety of approaches to an ethnomusicology of Inuit and Native North American musical expression. Contributors include Native and non-Native scholars who provide erudite and illuminating perspectives on aboriginal culture, incorporating both traditional practices and contemporary musical influences.